A new representation of Lagrange’s theorem in differential calculus - Mironenko, L.P.; Petrenko, I.V. (Искусственный интеллект, 2014)
It is found a new representation of the mean value Lagrange’s theorem in the differential calculus. Any
function increment can be expressed through the derivatives in the ending points of a given closed interval.
Mean values of the Lagrange derivative and our theory derivative are coincided, but the middle points are
different. Our theory allows easily find the middle point and it is not so easy according to Lagrange’s
theorem. Furthermore, our theory makes it possible to formulate the second mean value theorem in integral
calculus, as it is a consequence of differential theorem. У статті сформульовано нове представлення відомої теореми у диференційному численні про середнє –
теореми Лагранжа. Прирощення функції представлено через похідні у кінцевих точках відрізку.
Середнє значення похідної по Лагранжу і нашої теорії співпадають, але не співпадають середні точки.
Наша теорія дозволяє знайти середню точку, що важко зробити на підставі теореми Лагранжа. Крім
того, наша теорема дає можливість сформулювати теорему про середнє у інтегральному численні, бо
вона просто є наслідком диференціальної теореми. В статье сформулировано новое представление известной теоремы дифференциального исчисления о
среднем – теоремы Лагранжа. Приращение функции выражено через производные в концевых точках
отрезка. По величине среднее значение производной по Лагранжу и по нашей теории совпадают,
однако не совладают средние точки. Наша теория позволяет легко определить среднюю точку, что
затруднительно в теореме Лагранжа. Кроме того, наша теория дает возможность сформулировать
вторую теорему о среднем в интегральном исчислении, так как она является следствием дифференциальной теоремы.